Investigating the habitat selection and dietary preferences of a largely sedentary population of blue wildebeest in the Kgalagadi Transfrontier Park – impacts of permanent surface water provision in a semi-arid environment - Weeber, Joshua (Department of Environmental and Geographical Science, 2019)
The continued provision of waterholes since the early 1930s has facilitated the formation of a largely sedentary population of blue wildebeest (Connochaetes taurinus) in the Kgalagadi Transfrontier Park. However, other environmental variables may influence the distribution of this resident herd within the riverbeds of the Park. I explore the effects of water quality, forage abundance, tree density and river width on wildebeest habitat selection. I do this through a combination of an analysis of two years of wildebeest census data, published water quality data and a series of transects across the Auob and Nossob rivers for dung and grass sampling in the Park. My results show that water quality is a key predictor of wildebeest distribution, with animals strongly selecting for areas with access to fresh water over areas with saline or no water. Shade also emerged as a strong predictor of wildebeest distribution, demonstrating the importance of thermoregulatory behavioural adaptations in this arid savannah system. Wildebeest avoided areas of the riverbed that were densely vegetated, instead showing a preference for wider, open areas. This preference is likely a combination of two factors; enhanced predator detectability in open regions of the riverbed and the larger area of short grass communities present in this habitat. In this arid environment the distribution of available graze has long been considered an important variable in determining the distribution of wildebeest. I further examine my results showing that forage availability and quality plays a key role in wildebeest habitat selection through a stable carbon and nitrogen isotope analysis of wildebeest dung and the leaves of common shrubs and grasses to explore the spatial and temporal variation in wildebeest diet. These results show that wildebeest in my study site consumed a higher proportion of C3 plants than previously recorded in other areas of their range. This C3 intake increases in the dry season and in marginal, low use areas of the Park, suggesting that C3 plants are an important alternative food source to wildebeest during drought periods. This increase in C3 plants allow the animals to maintain their crude protein requirements throughout the dry season, despite a pronounced drop in the quality of available graze during this period. These results suggest that wildebeest were not food limited during the study period, although the distribution of these animals appears to largely reflect bottom up (resource based) mechanisms. A portion of the resident herd displayed some level of local movement, dispersing out of the riverbeds during the wet season before concentrating again near good quality waterholes in the dry season. This movement is likely driven by increased wet season forage outside the riverbed habitat and facilitated by ephemeral pools of water that form in pans in the rainy season. Grass species counts and grazing evidence were used to investigate the grazing habits of all herbivores in the riverbeds of the KTP. My results suggest that herbivores are more restricted in their grazing choices during the dry season. While there was no conclusive evidence to suggest that this was a direct result of grass quality, it is likely that the pronounced decrease in grass quality during the drier months does play a role in herbivore grazing habits.